Pengembangan E-Modul Berbasis Google Sites Terintegrasi Educandy Mata Pelajaran Pendidikan Pancasila Materi Kita Beragam Tetapi Tetap Satu Kelas II SDN Bangilan Bojonegoro - Nia Rohmatul Fadhilah; Midya Yuli Amreta; Muhammad Romadlon Habibullah (Global Action and Education for Society, 2026)
Digital technology offers significant opportunities in education through interactive learning media development. At SDN Bangilan Bojonegoro, Pancasila Education teaching remains conventional and monotonous, causing student disengagement and boredom. Teachers haven't utilized technology to create varied, engaging, and interactive materials. This study aimed to help second-grade students at SDN Bangilan understand diverse yet unified Pancasila Education content using a Google Sites-based e-module integrated with Educandy. The research employed Research and Development (R&D) methodology with the ADDIE model: Analysis, Design, Development, Implementation, and Evaluation. The study involved 13 second-grade students. Data collection included observations, interviews, documentation, and validation surveys from media experts, subject experts, and student trials (small and large scale). Validation results showed the e-module achieved